TROPES AND STYLE IN LONDON’S DISCOURSE ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
The article deals with the analyse how the author creates certain particular effects by the use of rhetorical sets; to characterize the type of language between literary norm and dialectal traits and features of colloquial language, and to classify the resources and the tropes in the construction of the created worlds. To study how Jack London creates a very special world, mainly by his descriptions of his characters. To distinguish the different voices (of narrators and characters), and how they sound in polyphony, in order to configure a world of representations, beliefs and opinions along these works.